Olfactory Signatures in the Food Finding Test in Mice With Normal and Alzheimer’s Disease-Pathological Aging With Special Concerns on the Effects of Social Isolation - Marín-Pardo, Daniela; Giménez-Llort, Lydia (Frontiers in Neuroscience, 2021)
The temporal course and the severity of the involution of sensory systems through aging can be critical since they ensure the ability to perceive and recognize the world. In older people, sensory impairments significantly increase their risk of biological, psychological, and social impoverishment. Besides, the olfactory loss is considered an early biomarker in Alzheimer’s (AD) neurodegenerative disease process. Here, we studied olfactory ethograms in middle-aged males and females of gold-standard C57BL/6 mice and 3xTg-AD mice, a genetic model of AD that presents cognitive dysfunction and a conspicuous neuropsychiatric-like phenotype. A paradigm involving one-day food deprivation was used to investigate the ethological patterns shown in the olfactory inspection of a new cage and the sniffing, finding, and eating of hidden food pellets. The sniffing-find-eat temporal patterns were independent of the loss of weight and unveiled (fast) olfactory signatures in Alzheimer´s disease differing from those (slow progressive) in normal aging. In 3xTg-AD mice, males exhibited an early signature than females, opposite to animals with normal aging. The sequence of actions was correlated in male and female 3xTg-AD mice in contrast to control mice. Social isolation, naturally occurring in 3xTg-AD males due to the death of cage mates, emphasized their olfactory patterns and disrupted the behavioral correlates. The paradigm provided distinct contextual, sex, and genotype olfactory ethogram signatures useful to investigate olfactory function in normal and AD-pathological aging. Isolation had an impact enhancing the changes in the olfactory signature here described, for the first time, in the 3xTg-AD model of Alzheimer’s disease.